Development of Nurses' Practical Educational Needs Scale for Women with Infertility - Jummi Park; Nayeon Shin; Kyungmi Lee; Junghyun Choi (Korean Society of Women Health Nursing, 2019)
PURPOSE: To develop nurses' educational needs scale for woman with infertility. METHODS: A total of 201 nurses in charge of infertility health services in 4 infertility hospitals and 1 public health center were enrolled for this study. The scale was developed through literature review, in-depth interview, development of preliminary items, verification of content validity, development of secondary items, verification of construct validity, and extraction of final items. Data were analyzed using item analysis, exploratory factor analysis, Pearson's correlation coefficients, and Cronbach's α. RESULTS: Nurses' educational needs scale for women with infertility consisted of 41 items. Three factors (education for disease and symptom of infertility, supporting and counselling for infertility patients, and education for daily life of infertile patients) explained 63.7% of the total variance. CONCLUSIONS: Nurses' educational needs scale for woman with infertility demonstrated acceptable validity and reliability. Its items could be used to assess the level of educational needs for nurses in charge of infertility health services.